2011
DOI: 10.1007/s00264-011-1277-8
|View full text |Cite
|
Sign up to set email alerts
|

Physeal injuries of the proximal humerus: long-term results in seventy two patients

Abstract: Purpose The aim of this study was to evaluate our treatment methods of proximal humeral physeal injuries retrospectively and elucidate the relationship between the trauma mechanism, the radiographic injury pattern, the consequent therapy and the functional outcome, and to further deduct and verify prognostic criteria. Methods At our Department of Trauma Surgery, 303 children and adolescent patients with fractures of the proximal humeral epiphysis were treated from 1992 to 2009. 72 cases were diagnosed as physe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Proximal humeral epiphyseal fractures are infrequently reported in both the human and veterinary literature. 15,16 Dissimilarly to that of companion animals, goat humeri characteristically possess unique anatomical variances that result in a dense region of bone located in close proximity to the body, which may further reduce the likelihood of proximal humeral fractures in this species. [5][6][7][8][9] Epidemiological studies in paediatrics have identified Salter-Harris type II fractures of the proximal humeral epiphysis to be the most common fracture configuration and often the result of high energy trauma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Proximal humeral epiphyseal fractures are infrequently reported in both the human and veterinary literature. 15,16 Dissimilarly to that of companion animals, goat humeri characteristically possess unique anatomical variances that result in a dense region of bone located in close proximity to the body, which may further reduce the likelihood of proximal humeral fractures in this species. [5][6][7][8][9] Epidemiological studies in paediatrics have identified Salter-Harris type II fractures of the proximal humeral epiphysis to be the most common fracture configuration and often the result of high energy trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Epidemiological studies in paediatrics have identified Salter-Harris type II fractures of the proximal humeral epiphysis to be the most common fracture configuration and often the result of high energy trauma. 15,16 Such trauma typically results in fractures propagating along epiphyseal scar lines, with muscle forces on fracture fragments and limb position at the time of impact also in consideration for fracture type and severity. 17 Isolated epiphyseal separation is rare and occurs typically in newborns and toddlers, 15 with treatment often conservative and consisting of shoulder immobilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Operative treatment should be considered when there is a marked displacement. 4,5 Operative treatment should be considered when there is a marked displacement.…”
Section: Introductionmentioning
confidence: 99%